The Impact of VEGF Inhibition on Clinical Outcomes in Patients With Advanced Non-Small Cell Lung Cancer Treated With Immunotherapy: A Retrospective Cohort Study - Tanimura, Keiko; Yamada, Tadaaki; Omura, Ayaka; Shiotsu, Shinsuke; Kataoka, Nobutaka; Takeda, Takayuki; Taniguchi, Ryusuke; Yamada, Takahiro; Takeuchi, Mayumi; Chihara, Yusuke; Morimoto, Yoshie; Iwasaku, Masahiro; et al. (Frontiers in Oncology, 2021)
Background: In recent years, immune checkpoint inhibitors (ICIs) in combination with chemotherapy have increased survival in patients with advanced non-small cell lung cancer (NSCLC). Vascular endothelial growth factor (VEGF), which plays a key role in tumor angiogenesis, is an immunological modulator; therefore, it is expected that anti-VEGF therapy in combination with ICIs enhances the antitumor effect of ICIs. In the present study, we investigated the impact of VEGF inhibition on clinical outcomes of NSCLC patients, including the efficacy of ICI treatment. Methods: A total of 105 patients with advanced NSCLC who had been treated with ICIs were retrospectively analyzed to examine the relationship between the history of treatment with anti-VEGF agents and the clinical outcomes with ICI monotherapy. Results: Patients who had received anti-VEGF therapy prior to ICIs showed shortened progression-free survival of ICI treatment and a decreased overall response rate to ICI treatment. By contrast, anti-VEGF therapy after ICI treatment was associated with increased survival, especially in patients who had also received anti-VEGF therapy prior to ICI therapy. Conclusions: These retrospective observations suggest that anti-VEGF therapy prior to ICIs might be a negative predictor of response to ICIs. The sequence of anti-VEGF therapy might play a role in its ability to predict survival in NSCLC patients. Further investigation is warranted to identify the role of VEGF inhibition in altering clinical outcomes after immunotherapy.